Mid-vastus total knee arthroplasty for medial osteoarthritis recovers gait balance control better than lateral parapatellar approach three months post-surgery - Lee, Pei-An; Wang, Ting-Ming; Chen, Yu-Ting; Wu, Kuan-Hsien; Liu, Hwa-Chang; Lu, Tung-Wu (Frontiers in Bioengineering and Biotechnology, 2023)
Total knee arthroplasty (TKA) approaches affect recovery outcomes, with different levels of residual loss of muscle strength and functional deficits. The current study compared the gait balance control in older individuals three months after TKA via the lateral parapatellar approach (LPPA) and mid-vastus approach (MVA) in terms of the inclination angle (IA) of the center of pressure (COP) to the body’s center of mass (COM) vector, and the rate of change of IA (RCIA). In a gait laboratory, 12 patients with severe medial knee osteoarthritis who had undergone bilateral TKA via LPPA and 12 via MVA were evaluated and compared against 12 healthy controls for their balance control during gait three months after surgery. The participants' kinematic data and ground reaction forces were measured synchronously using an 8-camera motion capture system and three forceplates, respectively, from which the COM, COP, IA and RCIA were calculated using a 13-body-segment model. The LPPA group showed significantly greater sagittal IA during DLS (p < 0.01) but less sagittal and frontal RCIA throughout the gait cycle (p < 0.04) compared to controls. The MVA showed better recovery in the balance control with most IA and RCIA variables similar to those of the healthy controls throughout the gait cycle. The patients with LPPA walked with a compromised balance control throughout the gait cycle while the MVA group showed close-to-normal balance control with a slight decrease in sagittal RCIA during SLS. The current between-approach findings were likely related to the differences in the muscles involved during surgery, suggesting that MVA may be a better choice than LPPA when taking short-term gait balance control into consideration.